2022
DOI: 10.21608/ejhm.2022.255202
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency Anemia in Children with Febrile Convulsions: A Case–control Study at Sohag University Hospital

Abstract: Background: Iron is necessary for healthy growth and development, and iron deficiency has been linked to behavioural problems, mental impairment, and reduced immunological function in children. Iron deficiency anemia (IDA) affects 48.5 percent of Egyptian preschoolers (aged 6 to 59 months). Objective: The aim of this study was to evaluate the iron status in children with first febrile seizure (FFS). Patients and Methods: This was a case-control hospital-based study that included children with febrile convulsio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…A predominant trend emerges in the comprehensive analysis of articles within this research, strongly supporting the significant relationship between ferritin levels and FS [ 5 - 9 , 11 , 12 , 19 , 21 , 24 , 26 , 27 ]. Nevertheless, there were notable exceptions among the findings.…”
Section: Reviewsupporting
confidence: 67%
See 4 more Smart Citations
“…A predominant trend emerges in the comprehensive analysis of articles within this research, strongly supporting the significant relationship between ferritin levels and FS [ 5 - 9 , 11 , 12 , 19 , 21 , 24 , 26 , 27 ]. Nevertheless, there were notable exceptions among the findings.…”
Section: Reviewsupporting
confidence: 67%
“…Among the 23 studies analyzed, five of which were conducted by Sharif et al, Yarigarravesh et al, Shaikh et al, Jang et al, and Tripathy et al reported that Hb exhibited no statistically significant association, with corresponding p-values of 0.06, 0.37, 0.44, 0.77, and 0.35, respectively [ 10 , 17 , 19 , 20 , 22 ]. The statistical significance of mean Hb levels was observed in all the studies except the one mentioned earlier [ 5 - 9 , 11 - 16 , 21 , 23 - 27 ].…”
Section: Reviewmentioning
confidence: 52%
See 3 more Smart Citations